2009
DOI: 10.1016/j.febslet.2008.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Leucine‐rich hydrophobic clusters promote folding of the N‐terminus of the intrinsically disordered transactivation domain of p53

Abstract: a b s t r a c t Molecular dynamics simulations have been performed on the intrinsically disordered 39-residue Nterminal transactivation domain of p53 (p53 1-39 ). Simulations not only revealed that p53 1-39 is natively compact, but also possesses a folded structure. Furthermore, leucine-rich hydrophobic clusters were found to play a crucial role in the formation and stabilization of the folded structure of p53 . Collapsing in the sub-microsecond timescale might allow for rapid conformational turnovers of p53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…As a recent study has shown [11], such interactions and hydrophobic cluster formation play an important role in folding of intrinsically disordered proteins and protein structure stabilization. A number of residues formed this hydrophobic cluster: Val 5 , Leu 4 , Leu 19 , Leu 21 , Val 34 , Leu 46 and Tyr 54 (see Figure S2 in supplementary material).…”
Section: Hydrophobic Clustermentioning
confidence: 99%
See 1 more Smart Citation
“…As a recent study has shown [11], such interactions and hydrophobic cluster formation play an important role in folding of intrinsically disordered proteins and protein structure stabilization. A number of residues formed this hydrophobic cluster: Val 5 , Leu 4 , Leu 19 , Leu 21 , Val 34 , Leu 46 and Tyr 54 (see Figure S2 in supplementary material).…”
Section: Hydrophobic Clustermentioning
confidence: 99%
“…Such type of complementary investigations have been proved to enlighten our knowledge of peptides/proteins structural properties and to help in better understanding of their action [9]. Recent simulation studies have enlighten our understanding of non-bonded interactions that stabilize secondary peptide structures [10] or promote folding [11]. One of the main targets of this study was to explore the five loop dynamics that connect the six strands region of PmrD'sˇ-barrel structure.…”
Section: Introductionmentioning
confidence: 99%
“…According to the current view, several IDPs, which are known to exploit crucial protein-protein interactions, can transiently populate, in their free state, pre-formed secondary structural elements, which are mainly a-helices and are often crucial for the molecular recognition (Belle et al, 2008;Espinoza-Fonseca, 2009a;Kjaergaard et al, 2010;Norholm et al, 2011;Sivakolundu et al, 2005;Wright and Dyson, 2009). Moreover, unbound IDPs can be characterized by globular conformations stabilized by intramolecular interactions of both electrostatic and hydrophobic nature (Brocca et al, 2011;Espinoza-Fonseca, 2009a;Frimpong et al, 2010;Marsh et al, 2007;Wostenberg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, unbound IDPs can be characterized by globular conformations stabilized by intramolecular interactions of both electrostatic and hydrophobic nature (Brocca et al, 2011;Espinoza-Fonseca, 2009a;Frimpong et al, 2010;Marsh et al, 2007;Wostenberg et al, 2011). Recently, atomistic or coarsegrained molecular dynamics (MD) simulations have been demonstrated to be an useful tool to describe the conformational landscape of the IDPs (Cino et al, 2011;Fisher and Stultz, 2011a,b;Ganguly et al, 2012;Qin et al, 2011;Rauscher and Pomes, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have been demonstrated to be a suitable technique to evaluate conformational ensemble of disordered peptides which consists of a variety of conformations [28][29][30][31]. In the this contribution, we present a molecular dynamics (MD) investigation of NPs in solution starting from their structure bound to the NPR-C [21,23] with the aim of providing a high-resolution atomistic view of their conformational ensemble in solution and of specific interactions that cannot be easily captured by experimental techniques [32][33][34].…”
Section: Introductionmentioning
confidence: 99%